The possible involvement of mitochondrial dysfunctions in Lewy body dementia: a systematic review - Spano, Mariangela (Funct Neurol, 2015)
The hallmark of dementia with Lewy bodies (DLB) is the “Lewy body”, an abnormal aggregation of alpha-synuclein found in some areas of the brain. The brain is the organ/system that is most vulnerable to this oxidative damage, and reactive oxygen species can cause neurodegenerative diseases. Different models of mitochondrial deregulation have been compared in DLB. The results are consistent with the hypothesis that alpha-synuclein affects the mitochondria themselves, increasing their sensitivity or leading to cell death through protective (neurosin) and accelerating (cytochrome c) factors. This systematic review suggests that mitochondria play an important role in neurodegeneration and a crucial role in the formation of Lewy bodies. DLB is a disease characterized by abnormal accumulation of alpha-synuclein that could result in the release of cytochrome c and subsequent activation of the apoptotic cascade.